2021
DOI: 10.1017/s1092852921000596
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between peripheral levels of inflammatory mediators and frontolimbic structures in bipolar disorder: an exploratory analysis

Abstract: Background Altered peripheral immune/inflammatory system and brain volumetric changes have been implicated in the pathophysiology of bipolar disorder (BD). This study aimed to evaluate how peripheral levels of cytokines are related to volumetric brain changes in euthymic patients with BD. Methods Euthymic patients with BD (n = 21) and healthy controls (n = 22) were enrolled in this exploratory study. Blood samples were collected on the same day of clinical assessment and neuroimaging. Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 55 publications
(83 reference statements)
1
9
0
Order By: Relevance
“…However, reviewing the studies on structural MRI, we qualitatively observe a tendency toward proinflammatory markers being more often associated with reduced volumes in several brain regions involved, for instance, in emotion regulation and somatomotor processing (Andreou et al, 2021;Bai et al, 2020;Chen et al, 2019;Mohite et al, 2021;Poletti et al, 2019;Tu et al, 2017), while anti-inflammatory ones were sometimes associated with larger volumes in different brain regions regulating affective processing (Mohite et al, 2021;Savitz et al, 2015). These findings might support the hypothesis of the neurotoxic effects of inflammation (Baharikhoob and Kolla, 2020;Benedetti et al, 2020;Giorgi et al, 2020Giorgi et al, , 2019Kim and Won, 2017;Saccaro et al, 2022), both peripheral and central (Felger, 2018), which may impact the volume of certain brain regions during development, or in adults, since, for instance, hippocampal adult neurogenesis may be affected by inflammation in animal models (Chesnokova et al, 2016;Haarman et al, 2016;Zonis et al, 2015) and in adult patients with schizophrenia, as suggested by indirect evidence on neurogenesis and inflammatory markers (Chesnokova et al, 2016;North et al, 2021).…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…However, reviewing the studies on structural MRI, we qualitatively observe a tendency toward proinflammatory markers being more often associated with reduced volumes in several brain regions involved, for instance, in emotion regulation and somatomotor processing (Andreou et al, 2021;Bai et al, 2020;Chen et al, 2019;Mohite et al, 2021;Poletti et al, 2019;Tu et al, 2017), while anti-inflammatory ones were sometimes associated with larger volumes in different brain regions regulating affective processing (Mohite et al, 2021;Savitz et al, 2015). These findings might support the hypothesis of the neurotoxic effects of inflammation (Baharikhoob and Kolla, 2020;Benedetti et al, 2020;Giorgi et al, 2020Giorgi et al, , 2019Kim and Won, 2017;Saccaro et al, 2022), both peripheral and central (Felger, 2018), which may impact the volume of certain brain regions during development, or in adults, since, for instance, hippocampal adult neurogenesis may be affected by inflammation in animal models (Chesnokova et al, 2016;Haarman et al, 2016;Zonis et al, 2015) and in adult patients with schizophrenia, as suggested by indirect evidence on neurogenesis and inflammatory markers (Chesnokova et al, 2016;North et al, 2021).…”
Section: Discussionmentioning
confidence: 88%
“…It should be noted that the samples of around 70 BD patients recruited in these two studies (Bai et al, 2020;Tu et al, 2017) are likely to be highly overlapping, although they are not identical. Another study on 21 BD patients identified a weakly significant (p=0.049) negative correlation between IFN-γ (a pro-inflammatory cytokine) and the volume of the right medialorbito-frontal cortex (OFC) (Mohite et al, 2021). Similarly, Chen et al (Chen et al, 2019) report a negative correlation between sIL-6R levels and OFC volume (as well as the volumes of lingual gyrus, inferior frontal cortex, middle frontal cortex, and planum polare).…”
Section: Structural Mri Correlates Of Inflammation In Bipolar Disordermentioning
confidence: 94%
See 3 more Smart Citations